2008
DOI: 10.1063/1.2972115
|View full text |Cite
|
Sign up to set email alerts
|

Dark carrier recombination in organic solar cell

Abstract: The carrier recombination in organic solar cells is investigated by numerical modeling to understand the weak dependence of the open-circuit voltage on the workfunction of the electrodes. In Ohmic contact structures, photocarriers recombine predominantly with dark carriers diffused from the electrode into the semiconductor. Such dark carrier recombination becomes the main limit of power conversion efficiency and open-circuit voltage. For a given semiconductor decreasing the workfunction difference of the elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 16 publications
2
19
0
Order By: Relevance
“…2 In contrast, for planar heterojunction (PHJ) cells recent models claim that V oc is almost independent of the electrode work functions. 12,13 This result was also supported by experimental findings. 12,14,15 The models attribute the weak work function dependence of V oc to band bending which partly compensates the change of the internal field.…”
Section: Introductionsupporting
confidence: 79%
“…2 In contrast, for planar heterojunction (PHJ) cells recent models claim that V oc is almost independent of the electrode work functions. 12,13 This result was also supported by experimental findings. 12,14,15 The models attribute the weak work function dependence of V oc to band bending which partly compensates the change of the internal field.…”
Section: Introductionsupporting
confidence: 79%
“…There are also several studies which addressed different reasons (considering different aspects) for the fact that higher mobilities may be unfavorable for device performance as a result of Voc reduction. For instance, authors of [26,51] showed that a reduction of Voc is due to recombination of dark charge carriers injected from the contacts as their density increases with the higher mobility.…”
Section: Ultimate Pce Map For Mobility-dependent (Lagevin Type) Lossesmentioning
confidence: 99%
“…[3][4][5][6][7] It has been shown that there is an optimum value of the mobility that leads to a peak efficiency. [3][4][5][6] Mobilities lower than the optimum value lead to lower efficiencies due to significant reductions in the dissociation rate of polaron pairs into free charge carriers, 3 together with less efficient charge extractions.…”
Section: Introductionmentioning
confidence: 99%